Edward's eyes - MacLachlan, Patricia (Atheneum Books for Young Readers, 2007)
Edward is one of a large and close family that loves baseball, music, books, and each other, and when he unexpectedly dies and his parents donate his organs, his wonderful eyes go to a perfect recipient.